PENGATURAN PENCEGAHAN UANG HASIL KEJAHATAN DALAM KEGIATAN INVESTASI USAHA - Muhammad Fathra Fahasta Fathra (JOURNAL EQUITABLE, 2020)
Evil is an act committed by a person or group of persons whose nature harms others. At this time the crimes are much developed either in the form of Corruption, Narcotics or other crimes. Along with the level of crime, the Government seeks to do the prevention and eradication with the rules of law to overcome it. Then from that writer do research about Stipulation of Money Result Of Crime In Business Investment Activity, this arise from writer observation either through mass media, development of crime rate of various forms lost the origin of crime in good way in the form of activity of Business Investment, join in Capital Market etc.